The fur Gene as a New Phylogenetic Marker for Vibrionaceae Species Identification - Machado, Henrique (Appl Environ Microbiol, 2015)
Microbial taxonomy is essential in all areas of microbial science. The 16S rRNA gene sequence is one of the main phylogenetic species markers; however, it does not provide discrimination in the family Vibrionaceae, where other molecular techniques allow better interspecies resolution. Although multilocus sequence analysis (MLSA) has been used successfully in the identification of Vibrio species, the technique has several limitations. They include the fact that several locus amplifications and sequencing have to be performed, which still sometimes lead to doubtful identifications. Using an in silico approach based on genomes from 103 Vibrionaceae strains, we demonstrate here the high resolution of the fur gene in the identification of Vibrionaceae species and its usefulness as a phylogenetic marker. The fur gene showed within-species similarity higher than 95%, and the relationships inferred from its use were in agreement with those observed for 16S rRNA analysis and MLSA. Furthermore, we developed a fur PCR sequencing-based method that allowed identification of Vibrio species. The discovery of the phylogenetic power of the fur gene and the development of a PCR method that can be used in amplification and sequencing of the gene are of general interest whether for use alone or together with the previously suggested loci in an MLSA.